Philo of Alexandria, the treatise On the Indestructibility of the World, and its relevance as a source of Ancient philosophy (Circe de clásicos y modernos, 2020)
The treatise On the Indestructibility of the World is one of Philo of Alexandria’s key philosophical texts. The way the Alexandrian “does philosophy” is idiosyncratic as an essential part of his method is based on his view that the Old Testament matches with what the Greek philosophers argue. In this paper, I argue that, despite that, Philo’s relevance as a source for the study of ancient philosophy can hardly be overestimated. To show that, I briefly first explain the structure of the treatise; secondly, I focus on the more “philosophical” sections to clarify how Philo incorporates some aspects of Platonism into his project of interpreting the Pentateuch in the light of Greek philosophy, and how, even though he takes distance from and criticizes the Stoics, at the same time he assimilates some terminolo-gical and conceptual details of Stoa as they are functio-nal to his own project.
Keywords: Philo; Platonism; Stoicism